Metabolite profiling of ascidian Styela plicata using LC-MS with multivariate statistical analysis and their antitumor activity - Satheesh Kumar Palanisamy; Daniela Trisciuoglio; Clemens Zwergel; Donatella Del Bufalo; Antonello Mai (Taylor & Francis Group, 2017)
To identify the metabolite distribution in ascidian, we have applied an integrated liquid chromatography- tandem mass spectrometry (LC-MS) metabolomics approach to explore and identify patterns in chemical diversity of invasive ascidian Styela plicata. A total of 71 metabolites were reported among these alkaloids, fatty acids and lipids are the most dominant chemical group. Multivariate statistical analysis, principal component analysis (PCA) showed a clear separation according to chemical diversity and taxonomic groups. PCA and partial least square discriminant analysis were applied to discriminate the chemical group of S. plicata crude compounds and classify the compounds with unknown biological activities. In this study, we reported for the first time that a partially purified methanol extract prepared from the ascidian S. plicata and Ascidia mentula possess antitumor activity against four tumor cell lines with different tumor histotype, such as HeLa (cervical carcinoma), HT29 (colon carcinoma), MCF-7 (breast carcinoma) and M14 (melanoma). S. plicata fraction SP-50 showed strong inhibition of cell proliferation and induced apoptosis in HeLa and HT29 cells, thus indicating S. plicata fraction SP-50 a potential lead compound for anticancer therapy. The molecular mechanism of action and chemotherapeutic potential of these ascidian unknown biomolecules need further research.